Implementation of Giving Equal Opportunities and Access to Work for Employees with Disabilities in MSME: A Case in Blitar, East Java - Nugroho, Arinto; Rusdiana, Emmilia; Ronaboyd, Irfa; Ocktavianti, Okky; Andreansyah, Gilang Chesar (Indonesian Journal of Disability Studies, 2024)
The obligation of private companies to empower at least 1% of persons with disabilities from the total number of employees is based on the mandate of the Law Number 8 Year 2016 on persons with disabilities and, at the provincial level, is regulated by the Regional Regulation of East Java Province Number 3 Year 2013. The purpose of this research is to provide an overview on the implementation of the obligation to provide equal opportunities and prepare access for employees with disabilities to Micro, Small and Medium Enterprises (MSMEs) business actors in the Blitar, East Java, Indonesia. The research method used is empirical law with a qualitative descriptive research approach. The stages of the research were carried out by conducting in-depth interviews and, at the same time observing by literature reviewing, data reduction, and then concluding. The results show that MSMEs in Blitar are willing to accept employees with disabilities. The employee recruitment process is carried out verbally and employment opportunities are prioritized to persons with disabilities who live nearby the company. Working hours and duration of break time for employees with disabilities are similar to the general employees. The obstacle faced by the company is the prohibition from the families of employees with disabilities to work because the disability employees are worried that they will not be able to do the job and are embarrassed when dealing with other people.